The effect of developing insurance marketing methods on performance of insurance companies (An applied research in the two Iraqi general and national insurance companies) - AL-LAMI, SUHA ABDULHASAN SHAIKHAH; ABBAS, MARYAM MUZSHIM; RUBBY, DR. KHLOOD HADI ABOOD AL (The journal of contemporary issues in business and government, 2021)
This research aims to introduce the importance of developing insurance marketing methods and their impact on the performance of insurance companies in general, and national and Iraqi insurance companies in particular, and what they can achieve from advantages and an increase in their competitive capabilities as well as contributing to reducing labor productivity costs and achieving efficiency and raising company performance. After reviewing the reality of the marketing activity in the national and Iraqi insurance companies, the researchers reached a set of recommendations that emphasize the importance of developing marketing methods to keep pace with global insurance companies, and take advantage of these advantages in the field of work in the company. The effect is also illustrated by changing the marketing services from traditional to electronic marketing, which works to reduce costs and reach the largest segment of targeted customers.